Posthumanism and Deconstructing Arguments Corpora and Digitally-driven Critical Analysis - O'Halloran, Kieran (Taylor & Francis, 2017)
Posthumanism and Deconstructing Arguments: Corpora and Digitally-driven Critical Analysis presents a new and practical approach in Critical Discourse Studies. Providing a data-driven and ethically-based method for the examination of arguments in the public sphere, this ground-breaking book: Highlights how the reader can evaluate arguments from points of view other than their own; Demonstrates how digital tools can be used to generate 'ethical subjectivities' from large numbers of dissenting voices on the world-wide-web; Draws on ideas from posthumanist philosophy as well as from Jacques Derrida, Gilles Deleuze and Félix Guattari for theorising these subjectivities; Showcases a critical deconstructive approach, using different corpus linguistic programs such as AntConc, WMatrix and Sketchengine. Posthumanism and Deconstructing Arguments is essential reading for lecturers and researchers with an interest in critical discourse studies, critical thinking, corpus linguistics and digital humanities.